PERKEMBANGAN UMKM PADA MASA PANDEMI COVID-19 - Dayu, Wulan; Pohan, Syahrial Hasanuddin; Hasibuan, Nurul Aswaliyah (Scenario (Seminar of Social Sciences Engineering and Humaniora); 2023, 2023)
The purpose of this study is to find out the efforts made by MSMEs to remain resistant in dealing with economic depreciation due to Covid-19. This research will describe in depth the new innovations made by MSMEs in marketing their products during the corona outbreak. the economic impact felt by SMEs due to the corona virus. This research will also examine the impact caused by marketing innovations that have been carried out by MSME entrepreneurs on their businesses. This research is a qualitative research with descriptive analysis method. The data collection method in this study used a questionnaire distributed via the Google form. The results of this study indicate that Covid-19 affects marketing practices carried out by small and medium enterprises. Marketing practices carried out switch to using online methods due to physical distancing or social distancing. In general, Covid-19 has reduced the sales turnover of micro, small and medium enterprises proportionally, but there are also several business sectors that have remained consistent and have even experienced an increase. The resistance of micro, small and medium enterprises is very high in dealing with the Covid-19 outbreak. This is due to the great confidence that micro, small and medium enterprises will survive until September.